Strukturalisasi Takwil Dalam Tafsir Ayat Mutasyābihāt: Studi Atas Kitab al-Tafsīr Al-Munīr Karya Wahbah Al-Zuĥaili - Fiki Khoirul Mala; Suci Ramadhan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Structuralization of Takwil in The Interpretation of The Mutasyābihāt Verse: Study of the Book of al-Tafsīr Al-Munīr by Wahbah Al-ZuĥailiThe interpretation of al-Qur’an as a tool in explaining Islam needs to be interpreted comprehensively. Combining the understanding of structuralization in the interpretation process is one of the efforts used by many interpreters of the Qur’an to interpret the verses of the Qur’an, such as Wahbah al-Zuĥaili. He is one of the interpreters who pays attention to the process of interpreting mutasyābihāt verses in his work al-Tafsīr al-Munīr. This study aims to analyze the process of structuralization of takwīl used by Wahbah al-Zuĥaili for the mutasyābihāt verses in the book al-Tafsīr al-Munīr. This is qualitative research with a linguistic approach that includes text and context study. The main data used is al-Tafsīr al-Munīr and supported by other books and scientific literature. Then, data were analyzed using content analysis. The study indicates that Wahbah al-Zuĥaili in doing takwīl on mutasyābihāt verses in al-Tafsīr al-Munīr pays great attention to the use of grammatical language combined with the meaning of the verse so as to produce new meanings that are in accordance with the needs of society at that time and modern society today. In addition, the incorporation of this understanding of structuralization has been able to break the monotony qur’anic interpretation today.